Extracorporeal life support with left ventricular decompression - improved survival in severe cardiogenic shock: results from a retrospective study - Schmack, Bastian; Seppelt, Philipp; Alt, Christina; Farag, Mina; Arif, Rawa; Dösch, Andreas; Raake, Philip; Karck, Matthias; Ruhparwar, Arjang (PeerJ, 2017)
Objective Extracorporeal life support (ECLS) is a life-saving procedure used in the treatment of severe cardiogenic shock. Within this retrospective single centre study, we examined our experience in this critically ill patient cohort to assess outcomes and clinical parameters by comparison of ECLS with or without selective left ventricular decompression. Methods Between 2004 and 2014 we evaluated 48 adult patients with INTERMACS level 1 heart failure (age 49.7 ± 19.5 years), who received either central ECLS with (n = 20, 41.7%) or ECLS without (n = 28, 58.3%, including 10 peripheral ECLS) integrated left ventricular vent in our retrospective single centre trial. Results Follow up was 100% with a mean of 0.83 ± 1.85 years. Bridge to ventricular assist device was feasible in 29.2% (n = 14), bridge to transplant in 10.4% (n = 5) and bridge to recovery in 8.3% (n = 4). Overall 30-day survival was 37.5%, 6-month survival 27.1% and 1-year survival 25.0%. ECLS support with left ventricular decompression showed favourable 30-day survival compared to ECLS without left ventricular decompression (p = 0.034). Thirty-day as well as long-term survival did not differ between the subgroups (central ECLS with vent, ECLS without vent and peripheral ECLS without vent). Multivariate logistic regression adjusted for age and gender revealed ECLS without vent as independent factor influencing 30-day survival. Conclusion ECLS is an established therapy for patients in severe cardiogenic shock. Independent of the ECLS approach, 30-day mortality is still high but with superior 30-day survival for patients with ECLS and left ventricular venting. Moreover, by unloading the ventricle, left ventricular decompression may provide an important time window for recovery or further treatment, such as bridge to bridge or bridge to transplant.
Gesehen am 06.03.2018